The mistakes of the Arabs and their mistakes in light Kanab Sibawayh A critical investigative study (Journal of the College of Basic Education, 2022)
The research was singled out for its subject, which is tagged with (the errors and mistakes of the Arabs in the light of a bookSibawayh - a single critical investigative study that has long aroused scholars' objection to the permissibleto her; Because of the pleasure it has on the lords of eloquence and its masters, and the first to establish this phenomenon in historyAbu Bishr Sibawayh in his book; As the oldest mature grammar work in our hands today; ThereforeI devoted myself to studying this phenomenon in his book. You might get me on closer examination (snoopingAnd the mistake) did not respond to the words of the Sheikhs of Sibawayh except in two places; And he accounted for the remainder +However, he did not exaggerate in misleading the Arabs. And what was mentioned in the multiplications of his book is something simple and modestscattered here and there; And I also learned that he did not misrepresent the meaning of (mistaking) the daughter} and whoClaiming otherwise was on a great deal of delusion and poor investigation. and that (mistake)